Going beyond 'regular and casual': development of a classification of sexual partner types to enhance partner notification for STIs. (29th April 2021) - Estcourt, Claudia S; Flowers, Paul; Cassell, Jackie A; Pothoulaki, Maria; Vojt, Gabriele; Mapp, Fiona; Woode-Owusu, Melvina; Low, Nicola; Saunders, John; Symonds, Merle; Howarth, Alison; Wayal, Sonali; et al.
Abstract : Objectives: To develop a classification of sexual partner types for use in partner notification (PN) for STIs. Methods: A four-step process: (1) an iterative synthesis of five sources of evidence: scoping review of social and health sciences literature on partner types; analysis of relationship types in dating apps; systematic review of PN intervention content; and review of PN guidelines; qualitative interviews with public, patients and health professionals to generate an initial comprehensive classification; (2) multidisciplinary clinical expert consultation to revise the classification; (3) piloting of the revised classification in sexual health clinics during a randomised controlled trial of PN; (4) application of the Theoretical Domains Framework (TDF) to identify index patients' willingness to engage in PN for each partner type. Results: Five main partner types emerged from the evidence synthesis and consultation: 'established partner', 'new partner', 'occasional partner', 'one-off partner' and 'sex worker'. The types differed across several dimensions, including likely perceptions of sexual exclusivity, likelihood of sex reoccurring between index patient and sex partner. Sexual health professionals found the classification easy to operationalise. During the trial, they assigned all 3288 partners described by 2223 index patients to a category. The TDF analysis suggested that the partner types might be associated with different risks of STI reinfection, onward transmission and index patients' engagement with PN. Conclusions: We developed an evidence-informed, useable classification of five sexual partner types to underpin PN practice and other STI prevention interventions. Analysis of biomedical, psychological and social factors that distinguish different partner types shows how each could warrant a tailored PN approach. This classification could facilitate the use of partner-centred outcomes. Additional studies are needed to determine the utility of the classification to improve measurement of the impact of PN strategies and help focus resources.